Gramáticas da criação: reflexões sobre um paradigma de crítica literária-teológica-religiosa / Grammars of creation: reflections on a paradigm of religious theological literary criticism - Paula, Adna Candido (Numen, 2014)
Resumo Este artigo apresenta e discute a prática da crítica literária-teológica-religosa, a partir da obra Gramáticas da criação, de George Steiner. Para tanto, problematiza a atribuição de valor ao objeto literário em uma perspectiva religiosa e ao objeto teológico-religioso em uma perspectiva literária. São apresentadas as considerações críticas de Steiner sobre o Livro de Jó, na dimensão religiosa-teológica, e sobre A Divina Comédia, de Dante Alighieri, na dimensão literária. Outrossim, indica a pertinência da reflexão de Steiner sobre as noções de “criação” e “invenção”, seus pontos de contato e de distanciamento. Como pano de fundo dessa discussão, desenvolvida em um panorama de argumentos que fazem a ponte entre a interdisciplinaridade e a transdisciplinaridade, está a questão da temporalidade humana. Palavras-chave: Crítica literária; criação; invenção; hermenêutica. Abstract This article presents and discusses the practice of religious theological literary criticism based on George Steiner’s Grammars of Creation. In order to do so, the present study problematizes value assignment to literary objects through a religious perspective and value assignment to theological religious objects through a literary perspective. The article also presents Steiner’s critical considerations on theBook of Job based on a religious theological dimension, and on Dante Alighieri’s The Divine Comedy through a literary point of view. In addition, it indicates the relevance of Steiner’s insights into the notions of “creation” and “invention”, their points of contact and distancing. As background to this discussion, grounded on a link between interdisciplinarity and transdisciplinarity, resides the question of human temporality. Keywords: Literary criticism; creation; invention; hermeneutics.